Higher Socioeconomic Status Predicts Less Risk of Depression in Adolescence: Serial Mediating Roles of Social Support and Optimism - Zou, Rong; Xu, Xia; Hong, Xiaobin; Yuan, Jiajin (Frontiers in Psychology, 2020)
Family socioeconomic status (SES) is known to have a powerful influence on adolescent depression. However, the inner mechanisms underlying this association are unclear. Here, we explore this issue by testing the potential mediating roles of social support (interpersonal resource) and optimism (intrapersonal resource), based on the predictions of the Reserve Capacity Model (RCM). Participants were 652 adolescents (age range: 11-20 years old, Mage =14.55 years, SD = 1.82; 338 boys (51.80%)) from two junior and two senior high schools in Wuhan, China. They completed questionnaires measuring family SES, perceived social support, trait optimism, and depression. Results showed, as predicted, (1) SES negatively predicted adolescent depression, (2) social support and optimism serially mediated the relations between SES and depression, consistent with the predictions by the RCM.Specifically, higher SES predicted greater social support and increased optimism, which in turn contributed to reduced depression. The implications of these data to the prevention and interventions of adolescent depression were discussed.